Karakteristik dan Aktivitas Antioksidan Pedada Beserta Turunannya - Lubis, Rizki Fadhillah; Putri, Gustiarini Rika; Siregar, Rahmad Syukur (REACTOR: Journal of Research on Chemistry and Engineering, 2020)
Indonesia is a country with the largest mangrove forests in the world. Indonesia also has various types of mangrove plants, one of which is pedada fruit (Sonneratia caseolaris). Pedada fruit is one type of mangrove whose fruit can be eaten. This fruit has good nutritional content and a source of vitamins A, B and C that are needed by the body. In addition, pedada fruit also contains phytochemical compounds that are closely related to antioxidant activity. With natural resources and abundant availability and nutrient content, pedada fruit is recommended to be used as processed food in order to increase food diversification. Pedada fruit has been processed into food processed products such as dodol, syrup, flour, ice cream, hard candy flavor, and jam. This study aims to study the characteristics of pedada fruit and its processed products into jam. Pedada fruit and jam have weak antioxidant activity values where the antioxidant activity is 549.91 ppm and 646.25 ppm, respectively.